Mechanisms for a nutrient-conserving carbon pump in a seasonally stratified, temperate continental shelf sea. (October 2019) - Humphreys, Matthew P.; Achterberg, Eric P.; Hopkins, Joanne E.; Chowdhury, Mohammed Z.H.; Griffiths, Alex M.; Hartman, Susan E.; Hull, Tom; Smilenova, Angelina; Wihsgott, Juliane U.; Woodward, E. Malcolm S.; Moore, C. Mark
Highlights: Seawater dissolved inorganic carbon and nutrients measured for 1.5 seasonal cycles. Inventories not in steady state from one winter to the next (e.g. 10% nitrate loss). Significant fraction of annual production stored in long-lived organic matter pool. Organic matter could provide mechanism for "continental shelf pump" carbon export. Abstract: Continental shelf seas may have a significant role in oceanic uptake and storage of carbon dioxide (CO2 ) from the atmosphere through a 'continental shelf pump' mechanism. The northwest European continental shelf, in particular the Celtic Sea (50°N 8°W), was the target of extensive biogeochemical sampling from March 2014 to September 2015 as part of the UK Shelf Sea Biogeochemistry research programme (UK-SSB). Here, we use the UK-SSB carbonate chemistry and macronutrient measurements to investigate the biogeochemical seasonality in this temperate, seasonally stratified system. Following the onset of stratification, near-surface biological primary production during spring and summer removed dissolved inorganic carbon and nutrients, and a fraction of the sinking particulate organic matter was subsequently remineralised beneath the thermocline. Water column inventories of these variables throughout 1.5 seasonal cycles, corrected for air-sea CO2 exchange and sedimentary denitrification and anammox, isolated the combined effect of net community production (NCP) and remineralisation on the inorganic macronutrient inventories. Overall inorganic inventory changes suggested that a significant fraction (>50%) of the annual NCP of around 3 mol-C m –2 yr –1 appeared to be stored within a long-lived organic matter (OM) pool with a lifetime of several months or more. Moreover, transfers into and out of this pool appeared not to be in steady state over the one full seasonal cycle sampled. Accumulation of such a long-lived and potentially C-rich OM pool is suggested to be at least partially responsible for the estimated net air-to-sea CO2 flux of ∼1.3 mol-C m –2 yr –1 at our study site, while providing a mechanism through which a nutrient-conserving continental shelf pump for CO2 could potentially operate in this and other similar regions.